Ground Water Recharge Techniques in India - Jha, Kumod Ranjan; Kumar, Gaurav; Gaur, Kanishk; Kumar, Dinesh; Bhardwaj, Ojesvi (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2014)
This paper is an Enquiry into the modern day techniques for recharging ground water, which are currently being employed in India. This paper also discusses some possible improvements in the current order of things.as we know the ground water is a crucial factor for any nation and for a country like India , where the population is increasing day by day this topic is of paramount importance. This paper gives sufficient material for a thorough overview of the issue.